A kind of methanol to propylene catalyst with anti-crushing property and its preparation method and application
The combination of ZSM-5 molecular sieve and rare earth or alkaline earth metal oxide additives is prepared to solve the problem of easy pulverization of the catalyst under high temperature hydrothermal conditions, and achieve long-term operation and efficient catalytic effects.
Patent Information
- Application Number
- CN202111644205.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-12-30
AI Technical Summary
The existing methanol-made propylene catalysts are prone to powder under high temperature hydrothermal conditions, resulting in reactor clogging and serious catalyst loss, making it difficult to meet the long-term operation needs of the industrial industry.
Using the combination of ZSM-5 molecular sieve, binder and rare earth or alkaline earth metal oxide additives, a catalyst that is resistant to crushing is prepared through a specific mass ratio and preparation process to improve its structural stability under high temperature hydrothermal conditions and Anti-crushing performance.
Under harsh conditions, the catalyst remains stable in structure, with a crushing rate below 5%. The first cycle operation life of the first cycle reaches 1,600 hours in industrial applications, excellent catalyst performance, methanol conversion rate>99.9%, propylene selectivity>47%, significantly better than the market Sale catalyst.
Smart Images

Figure BDA0003444587400000061 
Figure BDA0003444587400000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coal chemical catalysts, and specifically relates to a breakage-resistant methanol-to-propylene catalyst and a preparation method and application thereof. Background Art
[0002] Propylene is an important basic chemical raw material with a wide range of uses. It is one of the basic chemical products that affects the national economy and people's livelihood. With the rapid development of the national economy, the domestic demand for propylene has continued to increase in recent years. Domestic propylene is mainly obtained through the petroleum route, and the main propylene production methods in the petroleum route are steam cracking and catalytic cracking. my country's energy situation is "more coal, less oil, and lack of gas". From the perspective of national energy strategy, the production of propylene cannot rely entirely on the petroleum route. my country is rich in coal resources, and the development of coal chemical industry, especially coal-to-olefins, is of great strategic significance to ensuring the security of the national energy strategy and the clean use of coal.
[0003] The Dalian Institute of Chemical Physics of the Chinese Academy of Sciences, Shaanxi Xinxing Coal Chemical Technology Development Co., Ltd., and Sinopec Luoyang Petrochemical Engineering Co., Ltd. jointly developed the methanol to light olefins (DMTO) technology, using SAPO-34 as the active component of the fluidized bed catalyst and a circulating fluidized bed as the reactor. The products are mainly ethylene and propylene. This technology has been commercialized and has an industrial demonstration device. Sinopec has also developed a similar SMTO technology, which also uses SAPO-34 as the active component of the fluidized bed catalyst and a circulating fluidized bed as the reactor. Compared with the DMTO technology, the methanol space velocity of the SMTO technology is higher and the water ratio is 0. Tsinghua University has also developed the FMTP technology, which uses two reactors. The methanol conversion reactor uses SAPO-34 / SAPO-11 mixed crystal molecular sieve as the active component and a circulating fluidized bed as the reactor. The other reactor is a carbon-2-carbon-4 disproportionation to propylene (EBTP) reactor, and the final product is mainly propylene. Because SAPO-34 molecular sieve is easily deactivated by carbon deposition, these three technologies all use circulating fluidized bed reactors, with large catalyst loadings and severe losses.
[0004] Lurgi of Germany has developed a methanol to olefin fixed bed technology (WO2004 / 018089), using the ZSM-5 molecular sieve catalyst and fixed bed reactor of Southern Chemical Company to carry out methanol to olefin reaction, with a single-pass selectivity of propylene of 35-40%. CN102531823A, CN101172918B, CN101279280B, CN101402049A, and CN102211971A respectively disclose the process and catalyst preparation method of fixed bed methanol to propylene, using ZSM-5 molecular sieve as active component, using fixed bed reactor, and adopting the method of hydrocarbon recycling, that is, recycling C2, C4, C5+ hydrocarbons back to the fixed bed reactor to continue to react to generate propylene, thereby improving the selectivity of the target product.
[0005] In industrial applications, after the MTP catalyst has been running for a certain period of time, the catalyst will pulverize, blocking the reactor and causing an increase in the reactor pressure drop. As the running time increases, the pulverization problem becomes more and more serious, causing the reaction device to fail to operate normally and then shut down. In recent years, many domestic studies have focused on the problem of MTP catalyst pulverization, but for various reasons, it is difficult to simulate the high-temperature hydrothermal long-term operating environment of industrial equipment in the laboratory environment, and no breakthrough results have been achieved. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a methanol-to-propylene catalyst that is resistant to breakage, and a preparation method and application thereof. The catalyst prepared by the present invention has high structural stability and excellent anti-breakage performance under high-temperature hydrothermal conditions, and can achieve excellent methanol conversion rate and propylene selectivity in the methanol-to-propylene reaction.
[0007] The technical solution of the present invention is as follows: The present invention provides a breakage-resistant methanol-to-propylene catalyst, comprising: a ZSM-5 molecular sieve, a binder and an additive, wherein the mass ratio of the ZSM-5 molecular sieve, the binder and the additive is: (40-95): (4-59): (1-10), wherein the mass of the ZSM-5 molecular sieve and the binder is calculated on a dry basis, and the mass of the additive is calculated on a metal oxide basis;
[0008] The ZSM-5 molecular sieve is a hydrogen type; the additive is a rare earth metal oxide or / and an alkaline earth metal oxide, the rare earth metal is selected from one or more of cerium, neodymium, yttrium, praseodymium, lanthanum, europium, terbium, dysprosium, samarium and promethium, and the alkaline earth metal is selected from one or more of magnesium, calcium, strontium and barium. The addition of the additive fills the defective parts of the silicon-aluminum molecular sieve, which can significantly improve the structural stability of the molecular sieve under high-temperature hydrothermal conditions, and is conducive to enhancing the anti-crushing performance of the catalyst.
[0009] The present invention is further configured such that the mass ratio of the ZSM-5 molecular sieve, the binder and the auxiliary agent is: (60-85): (10-30): (3-7), wherein the mass of the ZSM-5 molecular sieve and the binder is calculated on a dry basis, and the mass of the auxiliary agent is calculated on a metal oxide basis.
[0010] The present invention is further configured such that the molar ratio of silicon oxide to aluminum oxide of the ZSM-5 molecular sieve calculated as silicon dioxide and aluminum oxide is 100 to 1000, and the grain size is 0.01 to 5 μm.
[0011] The present invention is further configured that the specific surface area of the catalyst is 300 to 450 m 2 / g, pore volume is 0.15~0.3cm 3 / g.
[0012] The present invention is further configured such that the binder comprises at least one of inert silicon dioxide and aluminum oxide.
[0013] The present invention is further configured that the source of the binder is one or more of pseudo-boehmite or kaolin.
[0014] The present invention is further configured such that the rare earth metal oxide or alkaline earth metal oxide is derived from one or more of the oxide, nitrate or carbonate of the rare earth metal or alkaline earth metal.
[0015] The present invention is further configured that the catalyst is heated to 580°C, 0.5 MPa, 58% methanol by mass content in methanol aqueous solution, and 10 h -1 The breakage rate after 8 hours of reaction under the conditions is: 0≤breakage rate≤5%.
[0016] The present invention provides a method for preparing the above catalyst, comprising the following steps:
[0017] (1) mixing ZSM-5 molecular sieve, a binder, a pore former and an additive in a certain proportion to obtain a uniform solid mixture;
[0018] (2) mixing the solid mixture obtained in step (1) and a peptizing agent in a certain proportion, kneading for 30-60 minutes, and then extruding to obtain a strip;
[0019] (3) Drying the strip obtained in step (2) at 120±10° C. for 4 to 8 hours, and then calcining at 500 to 600° C. for 4 to 8 hours to obtain a catalyst.
[0020] The present invention is further configured such that the pore-forming agent is selected from one or more of sesbania powder, flour, alkyl cellulose, guar gum and terephthalic acid, and the mass of the pore-forming agent is (1 to 10)% of the total mass of the ZSM-5 molecular sieve, binder and additive.
[0021] The present invention is further configured that the peptizing agent is an aqueous solution of one or both of nitric acid and citric acid, and the mass fraction of the acid in the peptizing agent is 0.5-10%.
[0022] The present invention also provides a method for preparing the above catalyst, comprising the following steps:
[0023] (1) mixing ZSM-5 molecular sieve, a binder and a pore-forming agent in a certain ratio to obtain a uniform solid mixture;
[0024] (2) mixing the solid mixture obtained in step (1) and a peptizing agent in a certain proportion, kneading for 30 to 60 minutes, and then extruding to obtain a strip;
[0025] (3) drying the strip obtained in step (2) at 120±10° C. for 4 to 8 hours, and then calcining at 500 to 600° C. for 4 to 8 hours to obtain a catalyst precursor;
[0026] (4) The catalyst precursor obtained in step (3) is immersed in the aqueous nitrate solution of the auxiliary agent for loading. After loading, the loaded catalyst precursor is calcined at 500-600° C. for 4-8 hours to obtain a catalyst.
[0027] The present invention is further configured such that the pore-forming agent is selected from one or more of sesbania powder, flour, alkyl cellulose, guar gum or terephthalic acid, and the mass of the pore-forming agent is (1 to 10)% of the total mass of the ZSM-5 molecular sieve and the binder.
[0028] The present invention is further configured that the peptizing agent is an aqueous solution of one or both of nitric acid and citric acid, and the mass fraction of the acid in the peptizing agent is 0.5-10%.
[0029] The present invention also provides an application of the above catalyst, wherein the catalyst is applied to a methanol to propylene reaction, wherein the reaction conditions are: a reaction temperature of 450 to 500°C, a reaction pressure of 0.01 to 0.5 MPa, and a methanol mass space velocity of 0.5 to 2 h -1 , the water content in methanol is 0 to 70%.
[0030] The present invention is further configured such that, in the reaction, the methanol conversion rate is greater than 99.9%, and the propylene mass selectivity is greater than 47%.
[0031] The present invention is further configured such that the reaction device is a fixed bed reactor.
[0032] The present invention has the following beneficial effects:
[0033] (1) The catalyst prepared by the present invention is operated in a crushing simulation test device for 8 hours, and the crushing rate is 0≤≤5%. It has a strong crushing resistance and can still maintain its original morphology under harsh conditions.
[0034] (2) The catalyst prepared by the present invention has a first cycle operating life of 1,600 hours in an industrial device for producing propylene from methanol, and the catalyst does not break. Its anti-breakage performance is significantly better than other similar catalysts on the market, which can meet the long-term operation requirements in industrial applications and reduce costs.
[0035] (3) The catalyst prepared by the present invention achieves a methanol conversion rate of >99.9% and a propylene mass selectivity of >47% in the catalytic methanol to propylene reaction, and has an excellent catalytic selectivity effect.
[0036] (4) The preparation process of the catalyst of the present invention is simple. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention is described clearly and completely below through embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments improved or modified by ordinary technicians in this field belong to the scope of protection of the present invention.
[0038] Example 1 Preparation of Catalyst
[0039] Weigh 95g of HZSM-5 molecular sieve, the silicon-aluminum ratio of HZSM-5 molecular sieve is 1000, the grain size is 0.01μm, 5.7g of high-viscosity pseudo-boehmite (70% alumina), 5g of sesbania powder, 5g of terephthalic acid, 1g of promethium nitrate, 0.5g of terbium nitrate, 0.5g of praseodymium nitrate and 0.5g of yttrium nitrate are mixed for 30 minutes; 45g of 0.5% nitric acid aqueous solution is added to the mixture, and after kneading for 30 minutes, a single-screw extrusion method is used to extrude strips using a perforated plate with a diameter of 3.0mm. The obtained strips are dried at 120°C for 8 hours, and calcined at 600°C in a muffle furnace for 4 hours to obtain a molecular sieve catalyst, marked as A-2.
[0040] Example 2 Preparation of Catalyst
[0041] 40 g of HZSM-5 molecular sieve with a silicon-aluminum ratio of 500 and a grain size of 1 μm were weighed, 86 g of macroporous pseudo-boehmite (70% alumina), 1 g of guar gum and 1 g of cerium oxide were mixed for 30 minutes, 45 g of 10% aqueous nitric acid solution was added to the mixture, and the mixture was kneaded for 60 minutes. The strips were hydraulically extruded using a 3.0 mm diameter orifice plate, and the obtained strips were dried at 120° C. for 8 hours and calcined at 500° C. in a muffle furnace for 4 hours to obtain a molecular sieve catalyst, which was marked as A-3.
[0042] Example 3 Preparation of Catalyst
[0043] Weigh 60g of HZSM-5 molecular sieve, the silicon-aluminum ratio of HZSM-5 molecular sieve is 100, the grain size is 5μm, 21g of pseudo-boehmite (70% alumina), 21g of kaolin, 3g of methyl cellulose, 3g of flour, 3g of samarium nitrate, 7g of neodymium carbonate, 5g of europium oxide and 2.5g of dysprosium nitrate are mixed for 30 minutes, 20g of 5% nitric acid aqueous solution and 25g of 0.5% citric acid aqueous solution are added to the mixture, kneading for 40 minutes, and extruding by a single screw extrusion method with a perforated plate with a diameter of 3.0mm. The obtained strips are left to stand at room temperature for 48 hours, dried at 120℃ for 4 hours, and calcined at 600℃ in a muffle furnace for 8 hours to obtain a molecular sieve catalyst, marked as A-4.
[0044] Example 4 Preparation of Catalyst
[0045] 74 g HZSM-5 molecular sieve with a silicon-aluminum ratio of 250 and a grain size of 0.5 μm was weighed, 20 g pseudo-boehmite (70% alumina), 15 g kaolin, 1 g magnesium nitrate, 1 g calcium carbonate, 0.6 g calcium oxide, 5 g guar gum and 2.5 g terephthalic acid were mixed for 30 minutes; 50 g 7% nitric acid aqueous solution was added to the mixture, kneaded for 30 minutes, and hydraulic extrusion was performed using a 3.0 mm diameter orifice plate. The obtained strips were dried at 120° C. for 4 hours, and calcined in a muffle furnace at 500° C. for 8 hours. The obtained catalyst was marked as A-5.
[0046] Example 5 Preparation of Catalyst
[0047] Weigh 73.5 g of HZSM-5 molecular sieve, the silicon-aluminum ratio of HZSM-5 molecular sieve is 200, the grain size is 0.5 μm, 35 g of pseudo-boehmite (70% alumina), 0.5 g of strontium oxide, 0.5 g of lanthanum oxide and 5 g of sesbania powder and mix for 30 minutes; add 30 g of 3% nitric acid aqueous solution and 15 g of 10% citric acid water to the mixture, knead for 30 minutes, and use hydraulic extrusion method with a 3.0 mm diameter orifice plate for hydraulic extrusion. The obtained strips are dried at 120° C. for 4 hours, and calcined at 500° C. in a muffle furnace for 8 hours. The obtained catalyst is marked as A-6.
[0048] Example 6 Preparation of Catalyst
[0049] Weigh 60g HZSM-5 molecular sieve, the silicon-aluminum ratio of HZSM-5 molecular sieve is 700, the grain size is 5μm, 21g pseudo-boehmite (70% alumina), 21g kaolin and 7g sesbania powder, mix for 30 minutes, add 45g 3.5% nitric acid aqueous solution to the mixture, knead for 40 minutes, adopt single screw extrusion method, use 3.0mm diameter perforated plate for extrusion, the obtained strips are dried at 120℃ for 6 hours, and calcined at 600℃ in a muffle furnace for 4 hours to obtain a catalyst precursor, the calcined strip catalyst precursor is impregnated with 100g 30% praseodymium nitrate aqueous solution at room temperature for 5 hours, the impregnation liquid is recovered, the obtained wet strips are dried at 120℃ for 4 hours, and calcined at 600℃ in a muffle furnace for 4 hours. The obtained catalyst is marked as A-7.
[0050] Comparative Example 1 Preparation of Catalyst
[0051] The preparation method of the catalyst is the same as that of Example 3, except that no auxiliary agent is added. The obtained catalyst is marked as A-8.
[0052] Control group
[0053] Commercially available catalyst, labeled A-1.
[0054] Example 7 Catalyst Characterization
[0055] In this example, the specific surface area and pore volume of the catalysts of Examples 1-6, Comparative Example 1 and the control group were measured by BET nitrogen adsorption method. The measurement results are shown in Table 1.
[0056] Table 1 Catalyst characterization results
[0057]
[0058] Example 8 Catalyst crushing experiment
[0059] The experimental device of this example is a small fixed bed reactor. 8g of A-4 catalyst particles with a diameter of 3mm and a length of 2mm are loaded into the reactor. The inner diameter of the reactor is 14mm, the catalyst bed height is 10mm, and inert alumina balls are installed above and below the catalyst. The reactor has three-stage temperature control and the temperature is measured in the center. The temperature is raised to 480℃, and nitrogen is filled to control the reactor pressure to 0.5MPa. Then the raw methanol aqueous solution (diluted with 42% water) is pumped into the top of the fixed bed reactor with a metering pump. The methanol mass space velocity is 10h -1 The reaction temperature was controlled to be maintained at 580°C. After 15 hours of reaction, the reaction was terminated, the catalyst was unloaded, and the catalyst breakage rate was measured. The breakage rate formula was: breakage rate = broken particle mass / total loading mass*100%. The breakage rate results of the A-4 catalyst are shown in Table 2.
[0060] Examples 9-15 Catalyst crushing experiment
[0061] The experimental method is the same as that of Example 8, except that the A-4 catalyst is replaced by A-1, A-2, A-3, A-5, A-6, A-7, and A-8, respectively. The results of the catalyst breakage rate are shown in Table 2.
[0062] Table 2 Catalyst crushing results
[0063] Catalyst name A-1 A-2 A-3 A-4 A-5 A-6 A-7 A-8 Crushing rate (%) 25.3 5.00 3.21 0 2.32 1.89 0.88 20.8
[0064] From the crushing test results of A-1 to A-8 in Table 2, it can be seen that the crushing rates of catalysts A-1 and A-8 without rare earth or alkaline earth metal oxide loading are both over 20%, while the crushing resistance rates of catalysts A-2 to A-7 loaded with rare earth and alkaline earth metal oxides are significantly improved. The catalysts prepared by the present invention all achieve a crushing rate of 0≤≤5% in the simulated crushing device, and their crushing resistance effect is significantly better than that of similar commercially available catalysts.
[0065] Example 16 Catalytic reaction of methanol to propylene
[0066] The experimental device of this example is a small fixed bed reactor. 2.5g A-4 catalyst was crushed into 10-20 mesh and loaded into the reactor. The inner diameter of the reactor was 14mm, and the catalyst bed height was 3.5mm. Inert alumina balls were installed above and below the catalyst. The reactor had three-stage temperature control and the temperature was measured in the center. The temperature was raised to 480℃ with nitrogen filling, and the device pressure was 0.03MPa. Then, methanol aqueous solution (diluted with 30% water) was pumped into the top of the fixed bed reactor with a metering pump. The methanol mass space velocity was 1h -1 The reaction temperature was controlled to be maintained at 480°C, and the reaction was continued for 10 days. Samples were taken and analyzed every 1 hour. At the end of the operation, the average values of the products within 10 days were calculated. The results of the catalytic reaction are shown in Table 3.
[0067] Example 17 Catalytic reaction of methanol to propylene
[0068] The experimental device of this example is a small fixed bed reactor. 2.5g A-3 catalyst was crushed into 10-20 mesh and loaded into the reactor. The inner diameter of the reactor was 14mm, and the catalyst bed height was 3.5mm. Inert alumina balls were installed above and below the catalyst. The reactor had three-stage temperature control and the temperature was measured in the center. The temperature was raised to 500℃ with nitrogen filling, and the device pressure was 0.01MPa. Then methanol was pumped into the top of the fixed bed reactor with a metering pump. The methanol mass space velocity was 2h -1 The reaction temperature was controlled to be maintained at 480°C, and the reaction was continued for 10 days. Samples were taken and analyzed every 1 hour. At the end of the operation, the average values of the products within 10 days were calculated. The results of the catalytic reaction are shown in Table 3.
[0069] Example 18 Catalytic reaction of methanol to propylene
[0070] The experimental device of this example is a small fixed bed reactor. 2.5g A-2 catalyst was crushed into 10-20 mesh and loaded into the reactor. The inner diameter of the reactor was 14mm, and the catalyst bed height was 3.5mm. Inert alumina balls were installed above and below the catalyst. The reactor had three-stage temperature control and the temperature was measured in the center. The temperature was raised to 450℃ with nitrogen filling, and the device pressure was 0.5Mpa. Then, methanol aqueous solution (diluted with 70% water) was pumped into the top of the fixed bed reactor with a metering pump. The methanol mass space velocity was 0.5h -1 The reaction temperature was controlled to be maintained at 480°C, and the reaction was continued for 10 days. Samples were taken and analyzed every 1 hour. At the end of the operation, the average values of the products within 10 days were calculated. The results of the catalytic reaction are shown in Table 3.
[0071] Examples 19-22 Catalytic reaction of methanol to propylene
[0072] The reaction conditions were the same as those in Example 17, except that the catalysts were replaced with A-1, A-5, A-6, and A-7 in sequence. The results of the catalytic reactions are shown in Table 3.
[0073] Table 3 MTP evaluation results
[0074]
[0075] From the results in Table 3, it can be seen that the catalysts A-2 to A-7 prepared by the present invention are used in the methanol to propylene reaction, and the methanol conversion rate is greater than 99.9%, and the propylene selectivity is greater than 47%; the catalyst prepared by the present invention has a higher methanol conversion rate and propylene selectivity for the methanol to propylene reaction than commercially available catalysts.
[0076] Example 23 Industrial Application of Catalyst
[0077] The catalyst prepared by the present invention is used in an industrial device for preparing propylene from methanol. The process conditions are: the methanol mass space velocity is 0.42 to 0.77 h -1 , steam mass air velocity 0.4~0.65h -1 , the mass space velocity of circulating hydrocarbon is 0.28~0.52h -1 , reaction temperature 460 ~ 490 ℃. After the first cycle of operation for 1600 hours, the catalyst did not break, and the average propylene yield was 27.57%; under the same conditions, the first cycle of commercially available catalysts was about 840 hours, and the average propylene yield was 25 ~ 26%.
[0078] In summary, the catalyst prepared by the present invention has excellent anti-breakage performance and excellent propylene selectivity and reaction life for the methanol to propylene reaction.
[0079] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A breakage-resistant methanol to propylene catalyst, characterized in that: include: ZSM-5 molecular sieve, a binder and an auxiliary agent, wherein the mass ratio of the ZSM-5 molecular sieve, the binder and the auxiliary agent is: (40-95): (4-59): (1-10), wherein the mass of the ZSM-5 molecular sieve and the binder is calculated on a dry basis, and the mass of the auxiliary agent is calculated on a metal oxide basis; The ZSM-5 molecular sieve is a hydrogen type; the auxiliary agent is a rare earth metal oxide or / and an alkaline earth metal oxide, the rare earth metal is selected from one or more of cerium, neodymium, yttrium, praseodymium, lanthanum, europium, terbium, dysprosium, samarium and promethium, and the alkaline earth metal is selected from one or more of magnesium, calcium, strontium and barium; The binder is derived from one or more of pseudo-boehmite or kaolinite. The molar ratio of silicon oxide to aluminum oxide in the ZSM-5 molecular sieve is 100 to 1000, and the crystal size is 0.01 to 5 μm. The specific surface area of the catalyst is 300 to 450 m 2 / g, pore volume is 0.15~0.3cm 3 / g; The catalyst is prepared by any one of the following two methods, wherein method 1 comprises the following steps: (1) mixing ZSM-5 molecular sieve, a binder, a pore former and an auxiliary agent in a certain proportion to obtain a uniform solid mixture; (2) mixing the solid mixture obtained in step (1) and a peptizing agent in a certain proportion, kneading for 30 to 60 minutes, and then extruding to obtain a strip; (3) drying the strip obtained in step (2) at 120±10° C. for 4 to 8 hours, and then calcining at 500 to 600° C. for 4 to 8 hours to obtain a catalyst; Method 2 comprises the following steps: (1) mixing a ZSM-5 molecular sieve, a binder and a pore-forming agent in a certain proportion to obtain a uniform solid mixture; (2) mixing the solid mixture obtained in step (1) and a peptizing agent in a certain proportion, kneading for 30 to 60 minutes, and then extruding to obtain a strip; (3) drying the strip obtained in step (2) at 120±10° C. for 4 to 8 hours, and then calcining at 500 to 600° C. for 4 to 8 hours to obtain a catalyst precursor; (4) impregnating and loading the catalyst precursor obtained in step (3) in a nitrate aqueous solution of the auxiliary agent, and after the loading is completed, calcining the loaded catalyst precursor at 500 to 600° C. for 4 to 8 hours to obtain a catalyst; The peptizing agent is one or both of nitric acid and citric acid in aqueous solution, and the mass fraction of the acid in the peptizing agent is 0.5-10%.
2. The breakage-resistant methanol-to-propylene catalyst according to claim 1, characterized in that: The mass ratio of the ZSM-5 molecular sieve, the binder and the auxiliary agent is: (60-85): (10-30): (3-7), wherein the mass of the ZSM-5 molecular sieve and the binder is calculated on a dry basis, and the mass of the auxiliary agent is calculated on a metal oxide basis.
3. The breakage-resistant methanol to propylene catalyst according to claim 1, characterized in that: The binder includes at least one of inert silicon dioxide and aluminum oxide.
4. The breakage-resistant methanol to propylene catalyst according to claim 1, characterized in that: The rare earth metal oxide or alkaline earth metal oxide is derived from one or more of the oxide, nitrate or carbonate of the rare earth metal or alkaline earth metal.
5. The breakage-resistant methanol to propylene catalyst according to claim 1, characterized in that: The catalyst is heated at a temperature of 580°C, a pressure of 0.5 MPa, a methanol aqueous solution containing 58% methanol by mass, and a methanol mass space velocity of 10 h -1 The breakage rate after 8 hours of reaction under the conditions is: 0≤breakage rate≤5%.
6. A method for preparing the catalyst according to any one of claims 1 to 5, characterized in that: The steps include: (1) mixing ZSM-5 molecular sieve, a binder, a pore former and an additive in a certain proportion to obtain a uniform solid mixture; (2) mixing the solid mixture obtained in step (1) and a peptizing agent in a certain proportion, kneading for 30 to 60 minutes, and then extruding to obtain a strip; (3) Drying the strip obtained in step (2) at 120±10° C. for 4 to 8 hours, and then calcining at 500 to 600° C. for 4 to 8 hours to obtain a catalyst.
7. The preparation method according to claim 6, characterized in that: The pore-forming agent is selected from one or more of sesbania powder, flour, alkyl cellulose, guar gum and terephthalic acid, and the mass of the pore-forming agent is (1-10)% of the total mass of the ZSM-5 molecular sieve, the binder and the auxiliary agent.
8. The preparation method according to claim 6, characterized in that: The peptizing agent is one or both of nitric acid and citric acid in aqueous solution, and the mass fraction of the acid in the peptizing agent is 0.5-10%.
9. A method for preparing the catalyst according to any one of claims 1 to 5, characterized in that: The steps include: (1) mixing ZSM-5 molecular sieve, a binder and a pore-forming agent in a certain ratio to obtain a uniform solid mixture; (2) mixing the solid mixture obtained in step (1) and a peptizing agent in a certain proportion, kneading for 30 to 60 minutes, and then extruding to obtain a strip; (3) drying the strip obtained in step (2) at 120±10° C. for 4 to 8 hours, and then calcining at 500 to 600° C. for 4 to 8 hours to obtain a catalyst precursor; (4) The catalyst precursor obtained in step (3) is immersed in the aqueous nitrate solution of the auxiliary agent for loading. After loading, the loaded catalyst precursor is calcined at 500-600° C. for 4-8 hours to obtain a catalyst.
10. The preparation method according to claim 9, characterized in that: The pore-forming agent is selected from one or more of sesbania powder, flour, alkyl cellulose, guar gum or terephthalic acid, and the mass of the pore-forming agent is (1-10)% of the total mass of the ZSM-5 molecular sieve and the binder.
11. The preparation method according to claim 9, characterized in that: The peptizing agent is one or both of nitric acid and citric acid in aqueous solution, and the mass fraction of the acid in the peptizing agent is 0.5-10%.
12. The use of a methanol to propylene catalyst resistant to breakage according to any one of claims 1 to 5, characterized in that: Applied to the methanol to propylene reaction, the reaction conditions are: reaction temperature of 450-500°C, reaction pressure of 0.01-0.5MPa, methanol mass space velocity of 0.5-2h -1 , the water content in methanol is 0 to 70%.
13. The use according to claim 12, characterized in that: In the reaction, the methanol conversion rate is >99.9%, and the propylene mass selectivity is >47%.
